Fecal microbiota transplantation from Suncus murinus, an obesity-resistant animal, to C57BL/6NCrSIc mice, and the antibiotic effects in the approach - Zhang, Mingshou; Sasaki, Hiraku; Yang, Ting; Chen, Juefei; Li, Rujia; Yi, Cheng; Li, Jun; He, Maozhang; Yi, Shuang-Qin (Frontiers in Microbiology, 2023)
Abstract Introduction: Important studies on the relationship of the intestinal microbial flora with obesity have uncovered profound changes in the composition of the gut microbiota in obese individuals. Animal studies successfully altered body phenotypes by fecal microbiota transplantation (FMT). Germ-free mice that received microbiota from human donors with obesity developed obesity. Methods: In this study, we analyzed the gut microbiome of Suncus murinus (S. murinus), a naturally obesity-resistant animal, and the changes of the gut flora of C57BL/NCrSIc mice that received gut bacteria transplantation from S. murinus by 16S rRNA gene analysis method. Results: Our results showed no significant changes in blood sugar or body weight in the FMT group compared to the control group, but large fluctuations due to antibiotics. The gut microbiota of S. murinus were enriched in Firmicutes and Proteobacteria, while Bacteroidetes were not detected, and fewer OTUs were detected in the intestine gut in comparison to other mouse groups. Statistically significant differences in alpha diversity were observed between the FMT group and other groups. Furthermore, a beta diversity analysis indicated an apparent structural separation between the FMT group and other groups. It was suggested that the gut flora of S. murinus was not well established in the gut trace of mice through FMT, and the administration of antibiotics before transplantation was an important factor affecting the overall composition of the gut flora. Conclusion: Although FMT of S. murinus failed to completely colonize the intestinal tract of the mice, it still had a certain effect on the establishment of the intestinal flora of the mice. The unpredictable effects of pre-transplantation antibiotics on the results of transplantation cannot be ignored.